The Impact of the Relationship between Supervisors of Commercial Banks and the Work of the External Auditor, a Study According to the International Auditing Standard (1004) - Majid Gazi Hasan; Ali Awadh Atshan; Waad Hadi Abd (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Purpose: This study aims to shed light on the relationship between the supervisors of commercial banks and the external auditor according to the international auditing standard 1004, and the complementary role between them. Reasonable whether the information contained in the basic accounting records and other sources of information is reliable and sufficient to prepare the financial statements. Theoretical framework: The theoretical framework of the study included several topics that were addressed to add introductory frameworks on the role of supervisors of the commercial bank, the elements of independence, objectivity and integrity of the independent external auditor, the responsibility of the bank's management and the relationship between bank supervisors and external auditors. Practical & Social implication: The supervisors of commercial banks whose main goal is to enhance the confidence of all parties related to the banking system. Therefore, they monitor the viability of the commercial bank at present and in the future in implementing its various activities by relying on the report of the external auditor on the financial position of the bank. Now the latter also takes into account the verification procedures. From the bank's commercial continuity in carrying out its current and future activities. Implications/Originality/Value: The possibility of activating the relationship between the supervisors of commercial banks in the Iraqi environment and the role played by the independent external auditor, as the supervisor is interested in maintaining a sound system of internal control as a basis for safe and careful management of the bank’s business, but the auditor is interested, in most circumstances, in assessing control to determine the degree of its dependence in planning and executing its work .